TOPOLOGY AND TOPOLOGICAL SPACE IN FINITE GEOMETRY WITH VARIABLES IN Zd (AUN INTERNATIONAL CONFERENCE, 2024)
In this paper, partial ordered relation is researched, finite geometry and its subgeometries are explored. An investigation of topology which exists in near-linear and non-near-linear finite geometry Gd is delved into. The outcome of this work shows an existence of the concept of topology and topological space on non-near-linear finite geometry with variables in Zd. The complexity shown in this work demonstrated the existence of relationship between a geometry as a structure and its subgeometries as its substructures.